Arabinogalactan from edible jambo fruit induces different responses on cytokine secretion by THP-1 macrophages in the absence and presence of proinflammatory stimulus - Tamiello, Camila Silva; do Nascimento, Georgia Erdmann; Iacomini, Marcello; Cordeiro, Lucimara M.C. (International journal of biological macromolecules, 2018)
Syzygium jambos is an Indo-Malaian found in many tropical countries and it is mainly composed of carbohydrates. Fraction PF-WSP and SF-WSP were obtained by aqueous extraction followed by Fehling’s treatment. Monosaccharide analysis showed that fraction PF-WSP has a high content of uronic acids (90%) and fraction SF-WSP presented mainly galactose (39.1%) and arabinose (34.2%), as neutral sugars and 9% of galacturonic acid. The presence of type II arabinogalactan in SF-WSP was evidenced by methylation analysis and 13C/1H HSQC NMR experiments. Immunomodulating properties of SF-WSP was investigated. It decreases THP-1 macrophage viability at the highest concentration tested (200μg/mL). We then tested non-cytotoxic concentrations of SF-WSP on THP-1 cytokine production in the presence and absence of LPS. The results showed that SF-WSP increased TNF-α, IL-1β and IL-10 secretion in a concentration-dependent manner as well as attenuated the inflammatory response induced by LPS at the highest concentration (100μg/mL). These results contribute to elucidate the effects of fruit pectic polysaccharides on immune cells.